2001
DOI: 10.1038/35052055
|View full text |Cite|
|
Sign up to set email alerts
|

Rab proteins as membrane organizers

Abstract: Cellular organelles in the exocytic and endocytic pathways have a distinctive spatial distribution and communicate through an elaborate system of vesiculo-tubular transport. Rab proteins and their effectors coordinate consecutive stages of transport, such as vesicle formation, vesicle and organelle motility, and tethering of vesicles to their target compartment. These molecules are highly compartmentalized in organelle membranes, making them excellent candidates for determining transport specificity and organe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

63
2,894
0
26

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 3,088 publications
(2,983 citation statements)
references
References 103 publications
63
2,894
0
26
Order By: Relevance
“…36,38,39 The time-course images showed that the majority of viral particles were first located in organelles that were positive for DsRed-Rab5 (Supplementary Intracellular trafficking of the engineered lentivirus K-I Joo and P Wang…”
Section: Tracking Of Viral Transport Through Endosomesmentioning
confidence: 99%
“…36,38,39 The time-course images showed that the majority of viral particles were first located in organelles that were positive for DsRed-Rab5 (Supplementary Intracellular trafficking of the engineered lentivirus K-I Joo and P Wang…”
Section: Tracking Of Viral Transport Through Endosomesmentioning
confidence: 99%
“…Rab proteins are a large family of small GTPases that regulate endosomal budding, sorting, movement and fusion within the cell. 69,70 As such, these proteins can act as 'zip codes' to facilitate endosome movement. Rab5 early endosomes can be routed to several destinations within the cell, of which the most relevant to AAVs are the late endosome (Rab7-positive compartment) 71 and the perinuclear recycling endosome (PNRE, Rab11-positive compartment).…”
Section: Receptor-mediated Endocytosis Of Aavmentioning
confidence: 99%
“…Rab GTPases coordinate endocytosis and can bind to many effector proteins thus facilitating and coordinating membrane/vesicular transport. More than 60 Rab proteins are known (Bruckert et al, 2000;Somsel Rodman and Wandinger-Ness, 2000;Moyer and Balch, 2001;Zerial and McBride, 2001). …”
Section: Trafficking and Sortingmentioning
confidence: 99%